Arm and shoulder morbidity following surgery and radiotherapy for breast cancer. (April 2014) - Johansen, Safora; Fosså, Kristian; Nesvold, Inger L.; Malinen, Eirik; Fosså, Sophie D.
Abstract Purpose. To explore the relationship between radiotherapy (RT) dose levels in the arm/shoulder region and arm/shoulder morbidity in breast cancer patients. Material and methods. This study included 183 breast cancer patients who had received locoregional RT with or without chemotherapy and/or hormone treatment during the period 1998–2002. Individual RT dose level, reflected by dose-volume histograms (DVHs), for the shoulder joint and joining structures were obtained from archived CT-based RT plans. Individual median, mean and maximum arm/shoulder RT dose levels were extracted. Arm/shoulder morbidity was assessed 29–58 months after breast cancer treatment using the following clinical endpoints: arm pain, arm stiffness, swollen arm, use of arm, numbness, shoulder flexion and shoulder abduction difference, fibrosis and breast cancer-related lymphedema. The relationship between arm/shoulder RT dose level and these clinical endpoints was assessed by Spearman's correlation and multivariate logistic regression. Results. Ninety-one percent of the included patients had some degree of arm/shoulder morbidity. Neither mean nor maximum RT dose level was associated with clinical endpoints. However, significant correlations (p < 0.05) were found between DVHs and arm stiffness, arm pain, use of arm and shoulder abduction difference, when arm/shoulder RT dose levels were approximately 15 Gy. Conclusions. Three-dimensional conformal locoregional RT for breast cancer results in long-term arm/shoulder morbidity. To minimize this risk, large shoulder volumes receiving RT doses of approximately 15 Gy should be reduced.